Three week results of transforaminal epidural steroid injection in patients with chronic unilateral low back related leg pain: The relation to MRI findings and clinical features - Ekedahl, Harald; Jönsson, Bo; Annertz, Mårten; Frobell, Richard B. (Journal of back and musculoskeletal rehabilitation, 2016)
BACKGROUND: Transforaminal epidural steroid injection (TESI) is a frequently used intervention for lumbar radicular pain. OBJECTIVE: To evaluate the value of MRI findings, neurologic assessment and the Slump test (neurodynamic test) as predictors of treatment response to TESI. METHOD: One hundred subjects (mean age 58 [SD13], 54% females) were included in this trial. The sample was stratified by location of disc herniaton, grade of nerve root compression, clinically assessed neurologic deficit and positive Slump test. Treatment response was primarily evaluated by Visual Analogue Scale for leg pain after three weeks. Predictive value for each stratum was analyzed using logistic regression after the sample was dichotomized into definite treatment response (≥ 50% reduction of pain) and negative response(≤ 0% reduction) to TESI (the 1-49% reduction group was excluded). RESULTS: The overall definite treatment response rate was 27%. The Slump test was the only predictor of the response to TESI (p= 0.031). The definite treatment response rates for subjects with positive and negative Slump test were 33% and 15%, respectively. CONCLUSION: In patients with chronic low back related leg pain, MRI findings and neurologic assessment results failed to predict treatment response, whereas a positive Slump test predicted the best 3-week response to TESI.